Senhoras de Andrade : o corpo, a dança e as novas tecnologias na obra de Moacir Andrade. - Fernandes Neto, João (2013)
When looking to study about the history of the city of Manaus, what is found in terms of study is most often directly linked to the period of the Rubber Cycle or the phase of the Manaus Free Zone, creating a large gap between a period and another. The 1950s, for example, constitute a period of great movement in Manaus: a process of resuming urbanization, population growth and cultural movement, as presented by Oliveira (2003), Mello (1984) and Souza (2003), showing a city that continued its activities, directly reflecting on what we are today in Manaus. The interest in developing this research arose from the need to seek to add other artistic languages ​​to the already recognized and solidified work of Moacir Andrade, who began his artistic trajectory in the mid-1950s and his contribution to the visual arts of Amazonas, bringing to the knowledge of all his commitment and its importance for the contribution of local cultural identity. To this end, this research seeks to answer the following question: How to re-present the works of the Amazonian artist Moacir Andrade in his paintings in the Amazon, enabling the exchange of Plastic Arts with contemporary Dance through the study and interpretation of his works in new artistic languages? To answer the question, we systematized this research and proposed the following specific objectives: to discuss the exchange of artistic languages ​​in the visual arts and dance, the reinterpretation of our works as well as their new interpretation and their greater dissemination to the population, enabling the meeting of artists of other languages ​​with works already established, to represent the painting of this great artist through contemporary dance and the use of new technologies. It is worth considering that the present research aims to discuss the existing relations between the visual arts and dance and how they influence the behavior and thinking of the contemporary body and how it assumes its role of transforming, reflective, questioning, thus contributing with new values ​​of contemporary art . To justify the research, we start from the assumption that without the linearity between the concepts, the body is explored in its unfolding, at the threshold between what emotion and reason coordinate and dance and gesture correspond. The research work starts from the process of studying open dance to confront, mix and investigate its potential through interaction with other artistic languages, especially the visual arts, which immerses itself in the grandiose work of the Amazonian artist Moacir Andrade, in his magical paintings about popular revelry in the Amazon. The re-presentation of these works gains a new concern, a new interpretation through the movement of these images, thus enabling greater diffusion and the reinforcement of our commitment to art in keeping our cultural identity more and more alive, adding even more values ​​to our artists as well as its popularization thus making our Brazilian cultural heritage increasingly rich. Iconographic sources will also have their place in the research, as they carry important information that can compose the final result. In addition to the sources described above, other documentary sources will also be searched, such as newspapers, magazines, folders, pamphlets that allow the crossing of information to deepen the issues that will be raised during the research process. As a final product of this research, 2 video dance works contextualized the re-reading of two works by Andrade and the dialogue with new technologies in this process of hybridization of the arts.